2022
DOI: 10.3233/jae-210018
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic plane wave diffraction by a cylindrical arc with edges: H-polarized case

Abstract: An accurate hybrid method (numerical-analytical method) for the diffraction of H-polarized electromagnetic plane wave by perfectly electric conducting cylindrical bodies containing edges and a longitudinal slit aperture is proposed. This method is the combination of the Method of Moment and semi-inversion method. The current density function is expressed as the Chebyshev polynomials forming a complete orthogonal set of basis functions. Then, the initial problem is reduced to a system of linear algebraic equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“… The comparison of the total field Hz ${H}_{z}$ distributions with (a) Orthogonal Polynomials Method for perfect electric conducting (PEC) surface [15], (b) embedding formulae method [17], and the proposed method with (ξ1=ξ2=0.001 ${\xi }_{1}={\xi }_{2}=0.001$) …”
Section: Numerical Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… The comparison of the total field Hz ${H}_{z}$ distributions with (a) Orthogonal Polynomials Method for perfect electric conducting (PEC) surface [15], (b) embedding formulae method [17], and the proposed method with (ξ1=ξ2=0.001 ${\xi }_{1}={\xi }_{2}=0.001$) …”
Section: Numerical Experimental Resultsmentioning
confidence: 99%
“…The present study proposes an analytical‐numerical approach to solve the corresponding equations provided in Equations () and (); the current densities on the circular strip are expressed as the summation of the Gegenbauer polynomials (Cnν+12) $({C}_{n}^{\nu +\frac{1}{2}})$ with unknown coefficients and the weighting coefficient 1η2νi ${\left(1-{\eta }^{2}\right)}^{{\nu }_{i}}$ to satisfy the edge condition as given in Equation (). It should be noted that the length of the arc is normalised by the change of variables as η=φθ $\eta =\frac{\varphi }{\theta }$ , φ=θη $\varphi =\theta \eta $ since the Gegenbauer polynomials are defined between [−1, 1] [13, 15]. μe(η)=1η2ν1n=0xnCnν1+12(η),0.25emμm(η)=1η2ν2n=0ynCnν2+12(η). ${\mu }^{e}(\eta )={\left(1-{\eta }^{2}\right)}^{{\nu }_{1}}\sum\limits _{n=0}^{\infty }{x}_{n}{C}_{n}^{{\nu }_{1}+\frac{1}{2}}(\eta ),\,{\mu }^{m}(\eta )={\left(1-{\eta }^{2}\right)}^{{\nu }_{2}}\sum\limits _{n=0}^{\infty }{y}_{n}{C}_{n}^{{\nu }_{2}+\frac{1}{2}}(\eta ).$ where xn ${x}_{n}$ and yn ${y}_{n}$ are the constant unknown coefficients.…”
Section: Formulation Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 provides the normalised near H-field distributions, and comparisons are made with both plane wave excitation and line source excitation of the circular strip with PEC surface, as referenced in Refs. [9,26], respectively. For PEC cases, the methodology of Refs.…”
Section: Comparison and Convergencementioning
confidence: 99%
“…For PEC cases, the methodology of Refs. [9,26] was employed to obtain Figure 3a,b. The observed deviation is less than 2%, indicating a reasonably close agreement between the results obtained in this study and those reported in the referenced works.…”
Section: Comparison and Convergencementioning
confidence: 99%